Beyond platinum: silver-catalyst based bubble-propelled tubular micromotors. Issue 23 (29th February 2016) - Teo, Wei Zhe; Wang, Hong; Pumera, Martin
Abstract : Tubular micromotors prepared with silver catalyst exhibited high mobility and could reduce reliance on scarce Pt metal. Abstract : There has been enormous interest in autonomous self-propelled micro-/nanomotors, especially those that relied on the decomposition of hydrogen peroxide fuel to generate oxygen bubbles and usually consisted of platinum on their surface which acts as an efficient catalyst. In this study, we developed Pt-free tubular micromotors by using a less expensive silver catalyst for bubble propulsion.